ANALISIS KONTRIBUSI DAN EFEKTIVITAS PENERIMAAN RETRIBUSI JASA UMUM TERHADAP PENDAPATAN ASLI DAERAH KOTA SAMARINDA - Elvyani NH. Gaffar (RJABM (Research Journal of Accounting and Business Management), 2017)
In building a region, it takes a very large funding input. Regional levies are among the largest contributors to regional development. Each region must be able to optimize its potentials to be able to increase local revenue (PAD). This study aims to determine: (1) the contribution of public services retribution on revenue of Samarinda years 2010-2016, (2) the effectiveness of public services retribution on revenue of Samarinda years 2010-2016, (3) effectiveness based sub sub- retribution public services on revenue of Samarinda years 2010-2016, (4) the contribution by sub retribution public services on revenue of Samarinda years 2010-2016. The type of research is descriptive research. The data used is secondary data, data collected by method of documentation recording. Using analytical tools contribution ratio and effectiveness. The results of this study indicate that: (1) The contribution of general service fees retribution to local revenue of Samarinda City year 2010-2016 is very less with average contribution rate of 9.65%. (2) The effectiveness of general service fees retribution to the original income of the city of Samarinda 2010-2016 is quite effective with an average effectiveness rate of 88.03%. (3) Of the twelve sub-receipts of general service fees retribution to the original revenue of Samarinda City in 2010-2016 as a whole is 70.48% or less effective. (4) Of the eleven sub-receipts of general service fee retribution to the original revenue of Kota Samarinda in 2010-2016 as a whole is 0.52% or very less